SURVEI KELINCAHAN DAN KECEPATAN PEMAIN FUTSAL PADA EKSTRAKURIKULER SMA NEGERI 7 BENGKULU SELATAN - Putra, H.; Syaputra, R.; Sembiring, L. T.; Sumantri, Ajis (Educative Sportive, 2024)
This study aims to determine the agility and speed of futsal players in the extracurricular of SMA Negeri 7 Bengkulu Selatan. This research uses quantitative descriptive. The method used is a survey. The population in this study were students of SMA Negeri 7 South Bengkulu, totaling 20 students. The sample used in this study were students of SMA Negeri 7 Bengkulu Selatan. The test instrument used was the zig-zag run agility test, and the speed of running 50 meters. Data using descriptive analysis techniques which are outlined in percentage form. The results showed that the ability of futsal players in the extracurricular of SMA Negeri 7 Bengkulu Selatan with the results for the agility test, the highest frequency category in the "medium" category, namely 10 players or 50%, the agility of the extracurricular futsal players of SMA Negeri 7 Bengkulu Selatan did not have a "very good" category in the category "good" 5 players or 25%, the category "medium" 10 players or 50%, the category "less" 4 players or 20% and the category "very less" 1 player or 5%. And for the speed test results, namely with the highest frequency category in the "medium' category, namely 14 players or 70%, the speed test for extracurricular futsal players of SMA Negeri 7 Bengkulu Selatan does not have a category of "excellent" which is categorized as "good" 2 players or 10%, the category "medium" 14 players or 70%, the category "less" 2 players or 10% and the category "very less" 2 players or 10%..